(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Food forensics is a scientific discipline that studies food origin, adulteration, and contamination through the use of scientific methods. In the same context, energy drinks also need to be analyzed from food forensics perspective, as they are consumed with an intent to provide energy to the body, owing to the presence of various macro and micro nutrients in it, like carbohydrates in from of sugars, caffeine, added vitamins, and other minerals, which also add to the popularity of these drinks. However, regular consumers of these drinks stand a chance of being more susceptible to be negatively impacted by the presence of certain metallic components present in these products. These metallic elements, especially heavy metals, can cause chronic and acute toxicity by various modes of action in both children and adults. The prerequisite for food authentication include reliable and precise analytical techniques due to the extreme competition in production of these drinks which leads to a high chance of consumer fraud. In this study, quantitative assessment of 10 heavy metals (Nickel (Ni), Copper (Cu), Zinc (Zn), Arsenic (As), Molybdenum (Mo), Cadmium (Cd), Tin (Sn), Barium (Ba), Mercury (Hg), Lead (Pb)) in energy drink samples of 10 different brands was carried out using microwave assisted acid decomposition and quantitation through ICP-MS instrument which is capable of analyzing several samples rapidly and permitted the identification of multiple metallic elements present in those samples which may be useful for investigations of food frauds in various legal issues. The study results however showed the presence of the selected heavy metals within the prescribed limit by FSSAI.